2019
DOI: 10.4018/978-1-5225-6286-3.ch012
|View full text |Cite
|
Sign up to set email alerts
|

Green Transformational Leadership and Organizational Behavior Effectiveness

Abstract: Green transformational leadership has been identified as the most effective leadership style where the leader seeks to change the status quo by transforming the organization and also considers achieving environmental goals and inspiring followers to perform beyond expected levels of environmental performance. Drawing insights from the literature on transformational leadership, this chapter examines the influence of green transformational leadership on organizational behavior effectiveness and environmental sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Based on the data analysis, the p -value is 0.001 < 0.050, so it can be concluded that there is a positive effect of Eco Training on Sustainable Corporate Performance. According to Ayandibu ( 2019 ) and Begum et al ( 2022 ) creating sustainable company performance requires Eco Human Resources Management (GHRM), in order to increase employee awareness for better quality and commitment to environmental sustainability. One of the important functions of GHRM is Eco Training.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the data analysis, the p -value is 0.001 < 0.050, so it can be concluded that there is a positive effect of Eco Training on Sustainable Corporate Performance. According to Ayandibu ( 2019 ) and Begum et al ( 2022 ) creating sustainable company performance requires Eco Human Resources Management (GHRM), in order to increase employee awareness for better quality and commitment to environmental sustainability. One of the important functions of GHRM is Eco Training.…”
Section: Resultsmentioning
confidence: 99%
“…Environmental protection and environmental performance of sustainable companies can be measured by a number of activities carried out by companies in the fields of waste management, pollution control systems, recycling, and mitigation of environmental releases. According to Ayandibu ( 2019 ) and Begum et al ( 2022 ) leadership is one of the most important management functions to achieve organizational goals, without a leader the organization will be less efficient and even unable to achieve the vision, mission, and goals specified. The success and continuity of the organization depends on the strength of the leadership because the leader is in charge of controlling the direction to be taken by an organization.…”
Section: Introductionmentioning
confidence: 99%
“…Companies are increasingly focusing on GC and GPD and production as green products and green management become more accepted and profitable (Ayandibu, 2019). As a result, fresh concepts for eco-friendly goods, procedures, or activities are regarded as valuable, creative, and innovative.…”
Section: Introductionmentioning
confidence: 99%